A new method for extracting microfluids using droplet technology - Hayder Kareem Hussein; Mustafa Abdulkadhim Hussein (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
An innovative and sensitive method for extracting liquid-liquid flour using pre-mixingwith the single-drop microextraction technique. This working system is distinguished by itsability to be applied to chemical and biological analyses. It is suitable for microfluidics, has ashort time, is free of contaminants, and has a simple design that can be installed anywhere inthe laboratory. The working system consists of several basic parts: a pump device to pump orfall back the organic and aqueous phase from the liquid-liquid micro-system through micro-rubber tubes and two precise micro-needles to generate drops, two mixers using two magneticclamps on two graduated holders, and a precise micro-mixer to complete the mixing process.Study of the main variables in the system containing dithizone (0.0001 M). ) in CHCl₃ solventsolution and aqueous copper chloride solution (1000 ppm) to see how they affect theextraction performance obtained by this method. The effect of the copper concentration in theinitial sample, the speed of the mixer, and the flow rate were discussed and studied, and thebest conditions were determined: for (2 ml) sample an aqueous solution of copper (II)chloride, the optimal concentration of copper. (II) in the analyzed sample is (0.0001M), thespeed of the micromixer is maximum, and the pump flow rate is (0.5 ml /sec). In theseoptimal conditions, the degree of extraction was (97±2%).